2015
DOI: 10.1002/tox.22204
|View full text |Cite
|
Sign up to set email alerts
|

Helioxanthin suppresses the cross talk of COX-2/PGE2 and EGFR/ERK pathway to inhibit Arecoline-induced Oral Cancer Cell (T28) proliferation and blocks tumor growth in xenografted nude mice

Abstract: Helioxanthin, an active compound from Taiwania cryptomerioides Hayata, has been shown to have various biological activities. However, their anticancer effect in oral squamous cell carcinoma has not been well established yet. Helioxanthin inhibited the proliferation of oral squamous cell carcinoma cells in a dose-dependent manner by inducing G2/M phase arrest. Similarly, helioxanthin inhibited cyclooxygenase-2, (COX-2), phosphorylated EGFR, and extracellular-signal-regulated kinases (ERK) protein level and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, arecoline has also been associated with the development of oral premalignant lesions and risk of oral cancer in many areas of Asia, the Pacific region, and in migrant communities in the United Kingdom, United States and South Africa where betel chewing is prevalent (Gupta and Warnakulasuriya, 2002; Sharan et al, 2012). Several animal studies have shown that arecoline administered by oral gavage to male mice induced lung adenocarcinoma and liver hemangioma (Bhide et al, 1984; Bhide et al, 1979), and chronic oral administration of arecoline through drinking water resulted in oral squamous cell carcinoma in mice (Lin et al, 2015b). However, arecoline was found not mitogenic to oral mucosal fibroblasts, and it causes cell cycle arrest of cultured oral KB epithelial cells (Chang et al, 2001; Tsai et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, arecoline has also been associated with the development of oral premalignant lesions and risk of oral cancer in many areas of Asia, the Pacific region, and in migrant communities in the United Kingdom, United States and South Africa where betel chewing is prevalent (Gupta and Warnakulasuriya, 2002; Sharan et al, 2012). Several animal studies have shown that arecoline administered by oral gavage to male mice induced lung adenocarcinoma and liver hemangioma (Bhide et al, 1984; Bhide et al, 1979), and chronic oral administration of arecoline through drinking water resulted in oral squamous cell carcinoma in mice (Lin et al, 2015b). However, arecoline was found not mitogenic to oral mucosal fibroblasts, and it causes cell cycle arrest of cultured oral KB epithelial cells (Chang et al, 2001; Tsai et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…16 Another study suggested that the mechanism of overexpressed COX-2 in promoting the proliferation of tumor cells is due to the role of Polygalacturonases (PGs), a product of COX-2 protein metabolism, especially PGE2, which enhances the proliferation of tumor cells. 30 The increase of PGE2 will not only inhibit the increase of T lymphocytes or B lymphocytes, but also induce the production of immunosuppressive cytokine IL-10. 31 Therefore, the body’s immune surveillance function is decreased, thereby increasing the probability of tumor cells proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was determined as mentioned previously by (Lin et al, ). NSCLC cells—A549, H520, and H661 cells (1 × 10 4 cells per well) and normal human bronchial epithelium cells ‐BEAS‐2B (5 × 10 3 cells per well) were seeded in 96‐well plate (Corning, NY).…”
Section: Methodsmentioning
confidence: 99%